STUDIES ON WALL HEATED MULTITUBULAR CATALYTIC PACKED BED REACTORSYSTEMHEATTRANSFER AND DYNAMICS - ABD ELGHAFOOR HASSAN, REEM HASSAN (2014)
Many vapor-phase exothermic chemical reactions are carried out in small diameter packed reactors in shell and packed tube heat exchanger configuration. Design of such units requires information on kinetics and transfer coefficients to facilitate scale up. Design of control strategy for safe operation and quality control requires information on system dynamics obtained by input-output analysis of the actual plant operation under dynamic operating conditions. This thesis reports experimental investigations on a pilot plant scale wall heated multi-tubular packed bed reactor converting isopropyl alcohol to acetone by dehydrogenation as a model reaction.